ESTABLISHMENT OF SOIL-GEOMORPHOLOGICAL MAPS USING GIS TECHNIQUES (FOR EXAMPLE, THE ALMATY REGION KARASAI) (Journal of Geography and Environmental Management, 2016)
It was found that the area Karasai is a very complex biogeosystems consisting of mountain and lowland parts, which are hierarchical landscape classification assigned to classes. The mountainous part of its composition has: highlands, midlands, low mountains. The plain consists of foothills , river valleys and low plains. They are classified as Division landscapes. On the basis of territorial analysis is made of soil - geomorphological map of scale 1:100 000.